Haemoglobin Status Of Pregnant Women An Analysis Of 1804 Cases - Quadrat-E-Elahi, M; Rahman, MM; Momtaz, S; Ferdousi, MA; Bhuyan, FA (Journal of Armed Forces Medical College, Bangladesh, 2012)
Introduction: Anaemia is a very common finding in Bangladeshi women. This is more common in pregnant women. Timely meet up of nutritional need successfully prevents the development of anaemia during pregnancy. Method: A cross-sectional and multi-centre study was carried out among 1804 pregnant cases at Child Welfare Centre (CWC) of Combined Military Hospitals (CMH) of Comilla, Savar and Bogra cantonments over a period of 19 months. Irrespective of ages all pregnant women who attended CWCs for routine ante-natal check up and whose blood haemoglobin level was known at the time of first visit were included in this study. Pregnant women with diabetes mellitus, hypertension and any congenital haemoglobin disorders were excluded from this study. Objectives: The aim of the study was to find out the haemoglobin levels in pregnant women in defence community from different parts of Bangladesh. Result: Total 1804 women were included as per inclusion criteria. Their mean (±SD) age was 28.1±13 years and the range was 19-41 years. Haemoglobin level during pregnancy was estimated and 229 (12.7%) of the pregnant women were observed anaemic. Most of the women had reported in the third trimester (40.8%) followed by second trimester (33.4%) and then first trimester (25.8%). Iron supplement was given to both normal and anaemic pregnant women. Conclusion: The study showed that prevalence and severity of anaemia in pregnant subjects attended CWCs for antenatal check up were exceptionally low. This indicates that consciousness regarding taking care of pregnant women of the community studied was satisfactory. DOI: http://dx.doi.org/10.3329/jafmc.v7i2.10390 JAFMC 2011; 7(2): 18-20